Nontraumatic oculomotor nerve palsy following endoscopic sinus surgery - Wasan F. Almarzouq; Salma S. Alsharhan (Wolters Kluwer Medknow Publications, 2024)
The proximity of the paranasal sinuses to the orbit and its contents increases the chances of injuries during endoscopic sinus surgery (ESS). We present an extremely rare case of transient oculomotor nerve palsy with no direct injury following ESS, which has never been reported in the literature. The proper clinical approach and medical management are also discussed in this case report.